Essentials of digital signal processing using MATLAB - Ingle, Vinay K.; Proakis, John G. (Australia : Cengage Learning Asia Pte Ltd, 2012)
In this title, practical examples are discussed and useful problems are explored.
1. INTRODUCTION.Overview of Digital Signal Processing. A Brief Introduction to MATLAB (R). Applications of Digital Signal Processing. Brief Overview of the Book.2. DISCRETE-TIME SIGNALS AND SYSTEMS.Discrete-time Signals. Discrete Systems. Convolution. Difference Equations. 3. THE DISCRETE-TIME FOURIER ANALYSIS. The Discrete-time Fourier Transform (DTFT). The Properties of the DTFT. The Frequency Domain Representation of LTI Systems. Sampling and Reconstruction of Analog Signals.4. THE z-TRANSFORM.The Bilateral z-Transform. Important Properties of the z-Transform. Inversion of the z-Transform. System Representation in the z-Domain. Solutions of the Difference Equations. 5. THE DISCRETE FOURIER TRANSFORM. The Discrete Fourier Series. Sampling and Reconstruction in the z-Domain. The Discrete Fourier Transform. Properties of the Discrete Fourier Transform. Linear Convolution Using the DFT. The Fast Fourier Transform. 6. IMPLEMENTATION OF DISCRETE-TIME FILTERS. Basic Elements. IIR Filter Structures. FIR Filter Structures. Lattice Filter Structures. Overview of Finite-Precision Numerical Effects. Representation of Numbers. The Process of Quantization and Error Characterizations. Quantization of Filter Coefficients.7. FIR FILTER DESIGN. Preliminaries. Properties of Linear-phase FIR Filters. Window Design Techniques. Optimal Equiripple Design Technique. 8. IIR FILTER DESIGN. Some Preliminaries. Some Special Filter Types. Characteristics of Prototype Analog Filters. Analog-to-Digital Filter Transformations. Lowpass Filter Design Using MATLAB (R). Frequency-band Transformations.9. SAMPLING RATE CONVERSION. Introduction. Decimation by a Factor D. Interpolation by a Factor I. Sampling Rate Conversion by a Rational Factor I/D. FIR Filter Designs for Sampling Rate Conversion. FIR Filter Structures for Sampling Rate Conversion.10. ROUND-OFF EFFECTS IN DIGITAL FILTERS. Analysis of A/D Quantization Noise. Round-off Effects in IIR Digital Filters. Round-off Effects in FIR Digital Filters.11. APPLICATIONS IN ADAPTIVE FILTERING. LMS Algorithm for Coefficient Adjustment. System Identification of System Modeling. Suppression of Narrowband Interference in a Wideband Signal. Adaptive Line Enhancement. Adaptive Channel Equalization.12. APPLICATIONS IN COMMUNICATIONSPulse-Code Modulation. Differential PCM (DPCM). Adaptive PCM and DPCM (ADPCM). Delta Modulation (DM). Linear Predictive Coding (LPC) of Speech. Dual-tone Multifrequency (DTMF) Signals. Binary Digital Communications. Spread-Spectrum Communications.
Includes bibliographical references and index.
Keywords: MATLAB